PARADOKS KEPATUHAN PAJAK UMKM INDONESIA: MODEL INTEGRATIF DAN IMPLIKASI PERGESERAN PARADIGMA KEBIJAKAN - A SYSTEMATIC LITERATURE REVIEW - Fransiskus Daniawan; Totok Dewayanto (Diponegoro Journal of Accounting, 2026)
This study diagnoses the dynamic mechanisms perpetuating tax non-compliance in Micro, Small, and Medium Enterprises (MSMEs) through an integrative conceptual model. Key variables examined include internal (capacity and literacy), external (incentives and administration), and psychosocial factors (tax morale and trust). A Systematic Literature Review (SLR) is employed to evaluate the effectiveness of traditional policies and formulate a novel relationship-centric framework.Methodologically, the SLR follows the PRISMA protocol, utilizing the PICO framework for research questions. Literature searches were conducted in the Scopus database targeting open-access English journal articles published between 2021 and 2025. From an initial 791 records, the screening and data extraction process yielded 35 high-quality articles for in-depth synthesis.The results confirm that MSME non-compliance is driven by a